Peran Creativity dan Innovative Mindsets Memediasi Entrepreneurship Education Terhadap Entrepreneurial Intention - Nilna Muna; Nyoman Sri Subawa (Ekuitas: Jurnal Pendidikan Ekonomi, 2022)
The purpose of this study was to examine the effect of entrepreneurship education on entrepreneurial intention: creativity and innovative mindsets mediate the effect of entrepreneurship education on entrepreneurial intention. This study used quantitative methods. Data collection techniques using offline questionnaires. Prior to this study, there were 96 students at the Monarch Vocational Training Institute in Bali, Indonesia. Path analysis is used to test hypotheses. The results of this study show that the effect of entrepreneurship education is not significant, and the effect of creativity on entrepreneurial intention is not significant. Entrepreneurship education, if done through innovative thinking, will have a positive and significant impact; if done through creativity, it will have a negative impact on entrepreneurial intentions. This means that innovative thinking is very important to increase entrepreneurial intentions. The practical implications of this research will benefit educational training institutions and governments as it clearly maps the factors that drive students' entrepreneurial intentions, enabling educational institutions to develop instructional programs that are responsive to environmental changes and adaptable to technological developments.